Mapping empire: two world maps in early medieval England - Appleton, H (Brepols, 2022)
This chapter focusses on two world maps preserved in an eleventh-century codex, London, British Library, MS Cotton Tiberius B V, in order to consider what great things these succinct representations of the world enabled their audience to know. Drawing on the work of Patrick Gautier Dalché, it argues for the importance of the viewing perspective afforded by a codex map to the interpretation of these images and their role in the manuscript.